2019
DOI: 10.1038/s41597-019-0141-3
|View full text |Cite
|
Sign up to set email alerts
|

Microbiomes of Velloziaceae from phosphorus-impoverished soils of the campos rupestres, a biodiversity hotspot

Abstract: The rocky, seasonally-dry and nutrient-impoverished soils of the Brazilian campos rupestre s impose severe growth-limiting conditions on plants. Species of a dominant plant family, Velloziaceae, are highly specialized to low-nutrient conditions and seasonal water availability of this environment, where phosphorus (P) is the key limiting nutrient. Despite plant-microbe associations playing critical roles in stressful ecosystems, the contribution of these interactions in the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 55 publications
0
23
0
Order By: Relevance
“…It is well accepted that the plant microbiome is shaped through a process of coevolution with its host under adverse environmental conditions ( Theis et al, 2016 ). Thus, further studies have suggested that plants in stressful ecosystems may harbor microorganisms capable of electing traits of tolerance to that unfavored condition ( Woodward et al, 2012 ; Camargo et al, 2019 ). A successful strategy of microbial selection aiming to further application in the field should consider microbiome origin as the first clue to microbial capabilities in an environmentally guided selection of traits.…”
Section: Designing Syncoms For Crop Resiliencymentioning
confidence: 99%
“…It is well accepted that the plant microbiome is shaped through a process of coevolution with its host under adverse environmental conditions ( Theis et al, 2016 ). Thus, further studies have suggested that plants in stressful ecosystems may harbor microorganisms capable of electing traits of tolerance to that unfavored condition ( Woodward et al, 2012 ; Camargo et al, 2019 ). A successful strategy of microbial selection aiming to further application in the field should consider microbiome origin as the first clue to microbial capabilities in an environmentally guided selection of traits.…”
Section: Designing Syncoms For Crop Resiliencymentioning
confidence: 99%
“…The different microbiomes of the two plants, despite their geographic proximity [27], suggests that contrasting substrates and host biology shape plant-associated communities in the campos rupestres . Furthermore, the finding that particular taxa become specialized on their host indicates that host and environment-specific pressures select specific functions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the siderophore repertoires of B. macrantha -associated communities were much larger, which could be interpreted as an indirect consequence of the higher abundance of the BGC-rich [56] Actinobacteriota in these microbiomes. We believe, however, that a complementary nutrient-driven explanation is also appropriate: as the iron content of the sampled rocks is around 8-fold lower than that of the soils [27] this nutrient is under increased demand in B. macrantha microbiomes, increasing the fitness of Actinobacteriota populations that are efficient at scavenging iron and, consequently, solubilizing phosphate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations